Critical Care for Coronavirus Disease 2019: Perspectives From the PICU to the Medical ICU. Issue 11 (November 2020) - Joyce, Christine L.; Howell, Joy D.; Toal, Megan; Wasserman, Emily; Finkelstein, Robert A.; Traube, Chani; Killinger, James S.; Joashi, Umesh; Greenwald, Bruce M.; Nellis, Marianne E.
Abstract : Objectives: To describe the unique perspective of pediatric intensivists caring for critically ill adults during the coronavirus disease 2019 pandemic. Design: Observational study. Setting: Academic medical center in New York City. Patients: Coronavirus disease 2019 positive adults requiring admission to an ICU. Interventions: None. Measurements and Main Results: In late March 2020, New York Presbyterian Hospital centralized all of its inpatient pediatric units ( n = 4) from across the network to a single center, in order to create space to accommodate the increasing number of critically ill adults with coronavirus disease 2019. Within 1 week, the PICU at New York Presbyterian Hospital-Weill Cornell Medicine transferred or discharged all inpatients, underwent a transformation of the physical space, and began admitting adults of all ages with coronavirus disease 2019 related acute respiratory failure. The New York Presbyterian Hospital-Weill Cornell Medicine PICU physician group continued to lead this unit. PICU nurses, respiratory therapists, social workers, and child life specialists joined their PICU physician colleagues to care for these critically ill adults. Conclusions: In the coronavirus disease 2019 pandemic, PICU physicians are well poised to care for adult patients in a surge capacity, and bring a unique perspective to the experience.